Deep Inferior Epigastric Perforator Flap with Implant Placement has a Favorable Complication Profile Compared with Implant-Only or Flap-Only Reconstruction - Wang, Carol; Roy, Nikita; Montalmant, Keisha E.; Shamamian, Peter; Seyidova, Nargiz; Oleru, Olachi; Graziano, Francis; Jacobs, Jordan M.S.; Sbitany, Hani; Henderson, Peter W. (Journal of Reconstructive Microsurgery, 2024)
Hybrid deep inferior epigastric perforator (DIEP) flap and simultaneous silicone implant breast reconstruction procedures (“DIEP + I”) have many conceptual advantages compared with either reconstruction method alone, but the outcomes of DIEP + I reconstruction have not yet been well studied. Therefore, the purpose of this study was to compare the outcomes of DIEP + I with implant-only and DIEP-only reconstruction.A retrospective review was conducted of patients undergoing DIEP + I, implant-only, and DIEP-only breast reconstruction from 2019 to 2023 at a single institution. Demographics and complication rates were compared between groups.A total of 145 patients were included in the DIEP + I (N = 26), implant-only (N = 59), and DIEP-only (N = 60) groups. The DIEP + I group had a lower overall complication rate than implant-only reconstruction (18.4 vs. 41.1%, p = 0.014), which was primarily due to the lower incidence of infections in the DIEP + I group (2.6 vs. 22.2%, p = 0.006). Accordingly, DIEP + I reconstruction decreased the odds of infection by 90% (OR = 0.095, p = 0.024) compared with implant-only reconstruction. The DIEP + I group had similar rates of wound healing and implant-related complications compared with the implant-only and DIEP-only groups, and no patients in the DIEP + I group experienced flap loss.DIEP + I breast reconstruction had a lower rate of infectious complications than implant-only reconstruction, and no higher rate of flap compromise or wound healing complications. This technique could be considered as a means of minimizing infection risk in patients with other risk factors who are seeking implant-based reconstruction, and of enhancing breast projection in patients who are seeking DIEP flap reconstruction.
Keywords: hybrid breast reconstruction; breast implants; DIEP flap; postoperative complications; comparative study; autologous reconstruction